2020
DOI: 10.1371/journal.pcbi.1007879
|View full text |Cite
|
Sign up to set email alerts
|

Towards a data-driven characterization of behavioral changes induced by the seasonal flu

Abstract: In this work, we aim to determine the main factors driving self-initiated behavioral changes during the seasonal flu. To this end, we designed and deployed a questionnaire via Influweb, a Web platform for participatory surveillance in Italy, during the 2017 − 18 and 2018 − 19 seasons. We collected 599 surveys completed by 434 users. The data provide socio-demographic information, level of concerns about the flu, past experience with illnesses, and the type of behavioral changes voluntarily implemented by each … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 59 publications
0
21
0
1
Order By: Relevance
“…Arguably, this may have played an important role in individual risk perception. We can speculate that reframing the emergency within a national dimension can amplify the perceived susceptibility of individuals [ 92 , 93 ] and thus increase the adoption of behavioral changes [ 4 , 94 ]. Indeed, previous studies showed that at the beginning of February 2020, people were overly optimistic regarding the risks associated with the new virus circulating in Asia, and their perception sharply changed after the first cases were confirmed in their countries [ 9 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arguably, this may have played an important role in individual risk perception. We can speculate that reframing the emergency within a national dimension can amplify the perceived susceptibility of individuals [ 92 , 93 ] and thus increase the adoption of behavioral changes [ 4 , 94 ]. Indeed, previous studies showed that at the beginning of February 2020, people were overly optimistic regarding the risks associated with the new virus circulating in Asia, and their perception sharply changed after the first cases were confirmed in their countries [ 9 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, data has demonstrated that individuals alter their behavior when there is a perceived risk of infection. 7 , 8 Identifying if certain subsets of society are more at risk of facial contact and the subsequent likelihood of self-inoculation may provide actionable data to stimulate behavior modification.…”
Section: Discussionmentioning
confidence: 99%
“…Such behavioral policies will need to be included in the theoretic model, in addition to pollen and meteorological variables, if we want to be able to understand the relative importance of social distancing versus seasonality. We could, for example, more explicitly include behavioral variables (Gozzi et al, 2020) in the compound model, by rating lockdown regimes on a Likert-type scale [1, 5], from no lockdown (1) to a complete lockdown (5). Although seasonal behavior might be implicitly covered by the meteorological variables, it could still make sense to model them more explicitly as there might be cultural patterns in play – such as holidays or seasonal celebrations – that need to be taken into account.…”
Section: Discussionmentioning
confidence: 99%